Business Ecosystem Approach to Industry 4.0 - Rossit, Daniel Alejandro (2021)
Industry 4.0 creates opportunities for defining new ways of creating value. Traditional manufacturing business models should be transformed to embrace its benefits. This transformation has the potential to induce changes not only in the shop-floor operation, but also on the strategies and processes supporting value creation activities. Most of the research focuses on engineering issues but not so much on how manufacturing firms shape their business, redefining their role in the business ecosystem, capturing more value thanks to network effects. The goal of this chapter is to lay the ground lines for a comprehensive business model for manufacturing firms, based on Industry 4.0 technologies. A Factory-as-a-Platform business model is proposed, illustrating it with a concrete example. The description of the platform-based business model embodies the answers to questions about how to make decisions regarding the core interaction among participants, how to grow-up the platform user base, how to monetize network effects, and to what extent should the platform be open.